2017
DOI: 10.1038/s41467-017-00568-7
|View full text |Cite
|
Sign up to set email alerts
|

Heparan sulfate proteoglycans present PCSK9 to the LDL receptor

Abstract: Coronary artery disease is the main cause of death worldwide and accelerated by increased plasma levels of cholesterol-rich low-density lipoprotein particles (LDL). Circulating PCSK9 contributes to coronary artery disease by inducing lysosomal degradation of the LDL receptor (LDLR) in the liver and thereby reducing LDL clearance. Here, we show that liver heparan sulfate proteoglycans are PCSK9 receptors and essential for PCSK9-induced LDLR degradation. The heparan sulfate-binding site is located in the PCSK9 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
78
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(87 citation statements)
references
References 63 publications
4
78
0
Order By: Relevance
“…First, we treated HepG2 cells with heparinase to remove cell surface heparin-like molecules (including HSPGs) prior to evaluating the effect of LDL on our PCSK9-NLuc uptake assay. Unsurprisingly, and consistent with prior results (31), heparinase treatment in the absence of LDL reduced PCSK9-NLuc uptake ( Fig. 2A, orange), with its absolute effect similar to that of pre-incubation of PCSK9 with LDL.…”
Section: Ldl Mediated Inhibition Of Pcsk9 Uptake Is Sensitive To Reagsupporting
confidence: 91%
See 3 more Smart Citations
“…First, we treated HepG2 cells with heparinase to remove cell surface heparin-like molecules (including HSPGs) prior to evaluating the effect of LDL on our PCSK9-NLuc uptake assay. Unsurprisingly, and consistent with prior results (31), heparinase treatment in the absence of LDL reduced PCSK9-NLuc uptake ( Fig. 2A, orange), with its absolute effect similar to that of pre-incubation of PCSK9 with LDL.…”
Section: Ldl Mediated Inhibition Of Pcsk9 Uptake Is Sensitive To Reagsupporting
confidence: 91%
“…Our initial results suggested that the cell-based factor might be directly competing with LDL to bind PCSK9 on a relatively slow kinetic timescale. We hypothesized that HSPGs on the HepG2 cells may be this cell-based factor, given the recent description of their affinity for the PCSK9 prodomain and involvement in PCSK9 uptake (31). To test this, we evaluated PCSK9 uptake with reagents expected to modify HSPG activity.…”
Section: Ldl Mediated Inhibition Of Pcsk9 Uptake Is Sensitive To Reagmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, LDL association may stabilize an autoinhibitory prodomain-CM1 interaction in PCSK9 that otherwise can be released by activating factors. Two such factors are known to improve the LDLR binding function of PCSK9, namely acidic pH (11,16,22) and its association with heparin-sulfate proteoglycans (HSPGs) at the surface of hepatocytes (59). HSPGs were recently shown to modulate the ability of LDL to inhibit PCSK9 activity, suggesting an interplay between these regulatory factors (23).…”
Section: Discussionmentioning
confidence: 99%